Impulse Buying Behavior of Consumers Through Social Commerce - Nguyen Thi Hai Binh (ZBW - Leibniz Information Centre for Economics, 2024)
The constant advancement of technology and the rise of social commerce have led to an increase in the inclination among consumers to make impulsive purchases while using social networking sites. It is crucial that researchers and social commerce merchants fully comprehend how the present social commerce environment might be used to manipulate consumers' impulsive buying behavior. So, utilizing the theory of planned behavior and the technology acceptance model, this study intends to analyze the impulsive purchasing behavior of Consumers using social commerce platforms in Vietnam. In response to this, convenience sampling combined with non-probability sampling has been adopted. In order to investigate and clarify the factors influencing user intention, data from 250 consumers were gathered via a questionnaire. These factors included perceptions of ease of use (EU), benefits of social commerce (BE), attitude toward purchasing behavior (AB), subjective norms (SB), control of purchasing behavior (BC), and behavioral intention (IB). The established questionnaire underwent formal validity and content validity checks by the expert panel to assure the validity and dependability of the survey tool. The results point to a variety of favorable influences on parameters that influence impulsive purchasing.
Keywords: 330; social commerce; impulse behavior; consumers